Generalised Operational Calculus Approach for Fractional Differential Equations - Fahad, Hafiz Muhammad (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2023)
Mikusinski’s operational calculus is a method for interpreting and solving fractional ´ differential equations, formally similar to Laplace transforms but more rigorously justified. This formalism was established for Riemann–Liouville and Caputo fractional calculi in the 1990s, and more recently for other types of fractional calculus. In this thesis, we consider the operators of Riemann–Liouville and Caputo fractional differentiation of a function with respect to another function, and discover that the approach of Luchko can be followed, with small modifications, in the more general settings too. We establish all the function spaces, formalisms, and identities required to build the versions of Mikusinski’s operational calculus which cover ´ Riemann–Liouville and Caputo derivatives with respect to functions. In the process, we gain a deeper understanding of some of the structures involved in applying Mikusinski’s operational calculus to fractional calculus, such as the existence of a ´ group isomorphic to R. The mathematical structure established here is used to solve fractional differential equations using Riemann–Liouville and Caputo derivatives with respect to functions, the solutions being written using multivariate Mittag-Leffler functions, in agreement with the results found in other recent work. It is useful to understand how the various operators of fractional calculus relate to each other, especially relations between newly defined operators and classical wellstudied ones. In this work, we also focus on an important type of such relationship, namely conjugation relations, also called transmutation relations. We define a general abstract setting in which such relations are relevant, and indicate how they can be used to prove many results easily in general settings such as fractional calculus with respect to functions and weighted fractional calculus.

ÖZ: Mikusinski’nin operasyonel kalkülüs metodu, kesirli diferansiyel denklemleri ´ yorumlama ve çözme yöntemi olup, biçimsel olarak Laplace dönü¸sümlerime benzese de daha detaylı dogrulanmı¸stır. Bu formalizm Riemann-Liouville ve Caputo kesirli ˘ kalkülüsleri için 1990’lı yıllarda belirlenmi¸s olup, ¸simdilerde diger kesirli kalkülüs ˘ çe¸sitleri için de kullanılmaktadır. Bu tezde, bir fonksiyonun Riemann-Liouville ve Caputo kesirli türevinin diger bir fonksiyona göre operatörleri ele alınmı¸stır ve ˘ Luchko’nun yakla¸sımının ufak degi¸sikliklerle daha genel durumlarda da ˘ kullanılabilecegi ke¸sfedilmi¸stir. Aynı zamanda, Mikusi ˘ nski’nin operasyonel kalkülüs ´ metodunun, fonksiyonlara baglı olarak Riemann-Liouville ve Caputo türevlerini ˘ kapsayan türlerini olu¸sturmak için gereken tüm fonksiyon alanları, formalizmler ve özde¸slikler belirlenmi¸stir. Bu süreçte, Mikusinski’nin i¸slemsel kalkülüsünü kesirli ´ kalkülüse uygulamada, reel sayılar kümesine izomorfik bir grubun varlıgı gibi yer ˘ alan yapılar daha derin biçimde kavranabilmi¸stir. Burada belirlenenen matematiksel yapı, Riemann-Liouville ve Caputo türevlerini fonksiyonlara göre kullanarak kesirli diferansiyel denklemleri çözmek için kullanılmı¸stır. Çok degi¸skenli Mittag-Leffler ˘ fonksiyonlarını kullanarak yazılan çözümler, yakın zamanda diger çalı¸smalarla ortaya ˘ çıkan neticelerle uyumludur. Çe¸sitli kesirli kalkülüs operatörlerinin, özellikle yeni tanımlanmı¸s ve hâlihazırda iyice çalı¸sılmı¸s olanların, birbiriyle olan ili¸skisini anlamak faydalıdır. Bu makale, bir diger ˘ adı dönü¸süm ili¸skileri olan, operatörler arası ili¸skinin önemli bir çe¸sidi konjugasyon ili¸skilerine odaklanmaktadır. Bu ili¸skilerin geçerli oldugu genel bir soyut durumu ˘ tanımlanarak, bunların fonksiyonlara baglı kesirli kalkülüs ve a ˘ gırlıklı kesirli kalkülüs ˘ gibi genel durumlarda birçok neticeyi kolayca ıspatlayabilmek için nasıl kullanılabilecekleri belirtilmi¸stir.
Doctor of Philosophy in Mathematics. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Mathematics, 2023. Supervisor: Assoc. Prof. Dr. Arran Fernandez.
Keywords: Thesis Tez; Mathematics Department; Fractional Calculus; Fractional differential equations; Mikusinski’s operational calculus; fractional calculus with respect to functions; algebraic conjugation; weighted fractional calculus